“Aclimatación de plántulas in vitro de yuca (manihot esculenta C.) en invernadero en la estación experimental el porvenir-Juan Guerra” - Ramirez Isuiza, Carlos Rafael (2013)
Presently work of investigation titled plántulas acclimatization in yucca vitro (Manihot esculenta C.) In Hothouse In The Experimental Station The Future - Juan Guerra. Whose study objectives were: To determine a protocol of acclimatization of yucca plántulas (Manihot esculenta C.), micropropagadas clonalmente under conditions of Laboratory, the effect of the inductor of growth sour indol butírico (AIB) in the good development of acclimatization in nursery of yucca plántulas (Manihot esculenta C.) spread in vitro.y the good levels of electric conductivity of a fertilizer solution to foliate balanced (20-20-20), which one carries out in the hothouse of Vegetable Biotechnology of the Agrarian Experimental Station "The Future", National lnstitute of Agrarian lnnovation - INIA, under a Design Totally at random (DCA) with factorial arrangement of 4 x 3 that he/she gave 12 treatments and 54 plántulas as a result for treatment, you concludes the following thing: lt was possible to obtain a protocol for the acclimatization of plántulas of Manihot escu/enta C in nursery lists for their transplant to definitive field. The Sour lndol butírico to dese of application of 2000 ppm and 3000 ppm responded satisfactorily in the parameters studied especially in the treatments Y23, Y33 and Y32 who highlighted more according to the analyses Duncan at the 0.05. You determines that the different levels of Electric Conductivity in the balanced fertilization (20-20-20), they influence in the best acting in Sour lndol Butírico on the plántulas of Manihot esculenta C in the different studied parameters. The good levels of electric conductivity used in the experiment, as 2.2 and 2.8, influence in a better assimilation from AIB to concentrations of 2000 and 3000 ppm whose effects are varied in function to the evaluated parameter, being this a-physiologic behavior of the same plant. Key words: Yucca (Manihot escu/enta C.), Acclimatization, Sour indolbutírico, electric conductivity.